Optimizing Education Processes During the COVID-19 Pandemic Using the Technology Acceptance Model - Tukiran, Martinus; Sunaryo, Widodo; Wulandari, Dian; Herfina, (Frontiers in Education, 2022)
The coronavirus disease 2019 (COVID-19) epidemic has become a significant global obstacle as it has impacted people's lives in various sectors, including social, economic, and education. To respond to the shock caused to education systems, massive efforts—such as conducting formal education through online classes—have been made. This study has employed Structural Equation Modelling (SEM) to examine this arena during the COVID-19 pandemic and has elaborated on how effectively the education system responded, especially through online lecturing. The Technology Acceptance Model (TAM) was implemented as this study’s theoretical framework. Partial Least Squares Structural Equation Modelling was employed to measure and assess the proposed model. This study was conducted through a survey with 112 student participants of a postgraduate program between January and December 2021. The findings showed that 1) the TAM-based proposed variables have been successfully explained during the pandemic through factors predicting the use by an online class of postgraduate students, 2) significant effects were reported from perceived ease of use and perceived usefulness toward actual system use through behavioral intentions to use, 3) there were no significant results to show an indirect effect from perceived ease of use and perceived usefulness toward actual system use through behavioral intentions to use.